Development of Learning Media Containing Socio Scientific Issue (SSI) to Improve Science Literacy Abilities in Green Chemistry Subject - Hanun Zahrotun Nisa; Julia Mardhiya; Apriliana Drastisianti (Journal of Educational Chemistry (JEC), 2026)
This study aims to develop and test the validity of learning media incorporating Socio-Scientific Issues (SSI) in green chemistry to improve students’ science literacy. The development of SSI-based media for green chemistry has not been sufficiently explored, even though this subject matter is conceptual and complex, causing students to often struggle to understand the concepts and relate them to everyday life. This study employed the Research and Development (R&D) method using the 4D development model, which includes the define, design, develop, and disseminate stages. The research subjects were 38 students in class X-J at SMAN 1 Cikampek. Data were collected using an expert validation questionnaire, a student response questionnaire, and a science literacy test in the form of essay questions. The results indicate that the instructional media achieved a high level of validity, with an Aiken’s V index of 0.89 from subject matter experts and 0.87 from media experts, thereby being deemed valid for use in instruction. Student responses to the media yielded excellent results, with an average percentage of 84.42%. Based on the paired sample t-test, a significance value of 0.000 < 0.05 was obtained, indicating a significant difference between students’ pretest and posttest scores. The effectiveness of the media was further supported by an N-Gain score of 0.6056 or 60.56%, which falls into the moderate category.  Based on these findings, the SSI-based learning materials were found to be valid, practical, and sufficiently effective in improving students’ science literacy in the area of green chemistry.